ROCK inhibition as a therapy for spinal muscular atrophy: understanding the repercussions on multiple cellular targets - Coque, Emmanuelle; Raoul, Cédric; Bowerman, Mélissa (Frontiers in Neuroscience, 2014)
Spinal muscular atrophy (SMA) is the most common genetic disease causing infant death, due to an extended loss of motoneurons. This neuromuscular disorder results from deletions and/or mutations within the Survival Motor Neuron 1 (SMN1) gene, leading to a pathological decreased expression of functional full-length SMN protein. Emerging studies suggest that the small GTPase RhoA and its major downstream effector Rho kinase (ROCK), which both play an instrumental role in cytoskeleton organization, contribute to the pathology of motoneuron diseases. Indeed, an enhanced activation of RhoA and ROCK has been reported in the spinal cord of an SMA mouse model. Moreover, the treatment of SMA mice with ROCK inhibitors leads to an increased lifespan as well as improved skeletal muscle and neuromuscular junction pathology, without preventing motoneuron degeneration. Although motoneurons are the primary target in SMA, an increasing number of reports show that other cell types inside and outside the central nervous system contribute to SMA pathogenesis. As administration of ROCK inhibitors to SMA mice was systemic, the improvement in survival and phenotype could therefore be attributed to specific effects on motoneurons and/or on other non-neuronal cell types. In the present review, we will present the various roles of the RhoA/ROCK pathway in several SMA cellular targets including neurons, myoblasts, glial cells, cardiomyocytes and pancreatic cells as well as discuss how ROCK inhibition may ameliorate their health and function. It is most likely a concerted influence of ROCK modulation on all these cell types that ultimately lead to the observed benefits of pharmacological ROCK inhibition in SMA mice.